2017
DOI: 10.1021/acscentsci.7b00115
|View full text |Cite
|
Sign up to set email alerts
|

Molecular, Local, and Network-Level Basis for the Enhanced Stiffness of Hydrogel Networks Formed from Coassembled Racemic Peptides: Predictions from Pauling and Corey

Abstract: Hydrogels prepared from self-assembling peptides are promising materials for medical applications, and using both l- and d-peptide isomers in a gel’s formulation provides an intuitive way to control the proteolytic degradation of an implanted material. In the course of developing gels for delivery applications, we discovered that a racemic mixture of the mirror-image β-hairpin peptides, named MAX1 and DMAX1, provides a fibrillar hydrogel that is four times more rigid than gels formed by either peptide alone—a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
138
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(144 citation statements)
references
References 83 publications
6
138
0
Order By: Relevance
“…Integration of 1‐ 13 C‐labeled amino acids was conducted in each sequence pattern of 2‐Nal‐substituted peptides as the incorporation of the heavier 13 C carbonyl group results in the shift of the amide I stretch due to the lower vibrational frequency. This shift of the amide I stretch is magnified when 13 C labeled carbonyls are in close proximity within the cross‐strand registry of a β‐sheet fibril, moving the signal to an even lower wavenumber . A substitution of each 2‐Nal sequence with a single 1‐ 13 C label at Lys 6 resulted in the amide I stretch shifting from ∼1616 cm −1 on the unlabeled peptides (Figure ) to ∼1600 cm −1 on the singly labeled peptides (Figure ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Integration of 1‐ 13 C‐labeled amino acids was conducted in each sequence pattern of 2‐Nal‐substituted peptides as the incorporation of the heavier 13 C carbonyl group results in the shift of the amide I stretch due to the lower vibrational frequency. This shift of the amide I stretch is magnified when 13 C labeled carbonyls are in close proximity within the cross‐strand registry of a β‐sheet fibril, moving the signal to an even lower wavenumber . A substitution of each 2‐Nal sequence with a single 1‐ 13 C label at Lys 6 resulted in the amide I stretch shifting from ∼1616 cm −1 on the unlabeled peptides (Figure ) to ∼1600 cm −1 on the singly labeled peptides (Figure ).…”
Section: Resultsmentioning
confidence: 97%
“…Solvent ionic strength, pH, and temperature strongly influence β‐sheet peptide self‐assembly and the emergent properties of the self‐assembled materials . In addition, peptide sequence order, repeat unit length (n), charge, and chirality also have a strong impact on self‐assembly . We and others, have shown that hydrophobicity and β‐sheet propensity are critical parameters for promoting the self‐assembly of amphipathic β‐sheet peptides .…”
Section: Introductionmentioning
confidence: 98%
“…Whereas strong experimental evidence has been provided by the Schneider and the Nillson laboratories that racemic mixtures of short peptides likely assemble to form rippled cross‐β configurations, there is, to the best of our knowledge, not a single high‐resolution rippled cross‐β structure available yet. The rac ‐Aβ40 system may offer a unique opportunity to obtain the first such structure in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The rac ‐Aβ40 system may offer a unique opportunity to obtain the first such structure in the future. There is a broad significance in the heterochiral molecular recognition phenomena that underlie the formation of rippled cross‐β structures, ranging from materials, as well as biomedical applications, to phenomena related to origins of life and chirality of biospheres …”
Section: Discussionmentioning
confidence: 99%
“…98 When the relative ratios of two gelators are mixed, we have also found that there can be a non-linear effect on the absolute moduli. 103 Interestingly, Nagy-Smith et al 106 have recently shown that mixing two gelators that are simply the enantiomeric isomers of each other results in the formation of a co-assembled system. The rheological data show that the co-assembled gel is much stiffer than those formed by either of the enantiomerically pure gelators.…”
Section: Multicomponent Systemsmentioning
confidence: 99%